Modewarre : Home Ground. - Sykes, Patricia (Spinifex Press, 2005)
What is home? What is identity? This collection features poems that set out on the winding paths of memory and aspiration in search of how these questions might be answered. Their context is local and universal, their voices restless and insistent. These poems seek to confront and understand the complex meanings of belonging.